2014
DOI: 10.1097/pas.0000000000000116
|View full text |Cite
|
Sign up to set email alerts
|

SALL4 Expression in Germ Cell and Non–Germ Cell Tumors

Abstract: SALL4 transcription factor is associated with embryonic cell pluripotency and has been shown as a useful immunohistochemical marker for germ cell tumors. However, information of SALL4 distribution in normal human tissues and non germ-cell tumors is limited. In this study we examined normal human tissues and 3215 tumors for SALL4 expression using a monoclonal antibody 6E3 and automated immunohistochemistry. In a 10th week embryo, SALL4 was expressed in ovocytes, intestine, kidney, and some hepatocytes. In adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(75 citation statements)
references
References 24 publications
3
72
0
Order By: Relevance
“…Analyses of its expression and epigenetic status have shown that SALL4 is de-regulated and aberrantly expressed in various cancers (Review in 64 ) such as leukemia 65 , germ cell tumors 6667 , hepatocellular carcinoma (HCC) 2468 , gastric cancer 20,6973 , colorectal carcinoma 7476 , esophageal squamous cell carcinoma 77,78 , breast cancer 7981 , endometrial cancer 82,83 , lung cancer 8486 and glioma 87 . Functionally, SALL4 is important for the survival 38,80,82,8893 , drug resistance 82,94 and metastasis 69,82 of many of these cancer cells (Figure 4).…”
Section: Sall4 In Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of its expression and epigenetic status have shown that SALL4 is de-regulated and aberrantly expressed in various cancers (Review in 64 ) such as leukemia 65 , germ cell tumors 6667 , hepatocellular carcinoma (HCC) 2468 , gastric cancer 20,6973 , colorectal carcinoma 7476 , esophageal squamous cell carcinoma 77,78 , breast cancer 7981 , endometrial cancer 82,83 , lung cancer 8486 and glioma 87 . Functionally, SALL4 is important for the survival 38,80,82,8893 , drug resistance 82,94 and metastasis 69,82 of many of these cancer cells (Figure 4).…”
Section: Sall4 In Cancersmentioning
confidence: 99%
“…In yolk sac tumors and primary extragonadal germ cell tumors, one study reported that the circulating tumor cells are detectable by anti-SALL4 antibody in peripheral blood samples, making this protein a more sensitive marker than α-fetoprotein and glypican-3 107 . In addition, SALL4 is expressed in a majority of malignant rhabdoid tumors (MRTs) 20108109110111 but rarely expressed in epithelioid sarcomas. Therefore, SALL4 immunoexpression may be a useful diagnostic tool to distinguish epitheloid sarcoma from malignant rhabdoid tumor.…”
Section: Sall4 In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar effects were noted with HDAC inhibitors, suggesting that the tumor suppressing effect of abrogating the SALL-NuRD interaction is dependent on reduction of NuRD complex associated HDAC activity. SALL4 overexpression has been noted in other tumors [90] and thus this strategy may have broader application as a new therapeutic target for specific cancers. An excellent candidate is uterine cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is plausible that disruption of SALL4-NuRD interaction in this tumor may also be beneficial. SALL family proteins are overexpressed or mutated in various cancers and its interaction with NuRD may emerge as an important mechanism for tumorogenesis or metastasis [90, 92, 93]. …”
Section: Introductionmentioning
confidence: 99%